Real-time immunization trends in under-2 children in Pakistan: insights from big data analysis. (30th September 2020) - Siddiqi, D A; Mirza, A; Abdullah, S; Dharma, V K; Shah, M T; Akhter, M A; Habib, A; Khan, A J; Chandir, S
Abstract: Background: Despite the provision of free-of-cost vaccines in Pakistan, fully immunized child (FIC) coverage in Sindh province remains low at 49%. In 2012, we developed and piloted the Zindagi Mehfooz (Safe Life; ZM) Digital Immunization Registry, an Android-based platform that enables vaccinators to enroll and track child level immunization data of children in the catchment population. In 2017, ZM was scaled-up across Sindh province and is currently being used by 2, 284 vaccinators across 1, 526 facilities serving >48 million (m) population. Methods: All children under-2 years of age visiting EPI centers are enrolled. At enrollment, caregiver and child bio-data and child immunization history are recorded, and the child is provided with a unique Quick Response (QR) code for identification. For follow-up immunization visits, 3 SMS reminders are sent to caregivers, and upon immunization, child history is retrieved by scanning the QR code and vaccination record updated. ZM allows real-time access to data and generation of monitoring reports. Data from ZM was used to calculate coverage rates, timeliness, and trends for immunization coverage in Sindh. Results: From Oct'17 to Dec'19, more than 2.4m children and 0.8m women were enrolled in the Registry, while >17m immunizations were administered. The FIC coverage in 12-23 months old children has increased from 49% (at baseline) to 57% for children enrolled in ZM. Additionally, pentavalent-3 coverage increased from 59% to 68%. Discussion: ZM demonstrates the potential of DIRs to improve immunization outcomes within low-resource settings by enabling better child tracking and a higher retention rate. Additionally, the big dataset provides the opportunity to identify real-time trends and provides actionable data for evidence-based decision making. Key messages: ZM Immunization Registry has strengthened the current EPI program through increased FIC coverage and timeliness through better tracking of children and increased retention. Big Data from ZM can be used to analyze immunization trends of global relevance, and guide strategic policy decisions for improving immunization coverage and equity, based on actionable data insights.